Transition metal doped polyoxometallate cluster as well as preparation method and application thereof

By adopting transition metal doped polyoxylate clusters such as Na34[Co19(OH)12(SiW10O37)6]·46H2O, the problems of catalyst instability and insufficient OER performance in the prior art are solved, and efficient Electrocatalytic oxygen evolution reaction, and its performance is close to that of commercial precious metal catalysts.

CN119461400APending Publication Date: 2025-02-18ZHENGZHOU UNIVERSITY OF LIGHT INDUSTRY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411247571.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-06
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

In the prior art, transition metal doped polyoxylate clusters have insufficient performance in electrocatalytic oxygen evolution reactions, and there are problems such as unstable catalysts, few catalytic active sites, unclear catalytic mechanisms, and insufficient OER performance as well as commercial catalysts. .

Method used

Using transition metal doped polyoxylate clusters such as Na34[Co19(OH)12(SiW10O37)6]·46H2O, an electrical circuit containing high core number cobalt-oxygen clusters is formed through specific molecular structural units and preparation methods. catalyst.

Benefits of technology

It achieves better OER performance, low overpotential, small slope of Taffir, many catalytic active sites, and close to commercial precious metal catalysts. It has simple preparation technology, cheap raw materials, and easy to mass production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119461400A_ABST
    Figure CN119461400A_ABST
Patent Text Reader

Abstract

The invention discloses a transition metal doped polyoxometallate cluster as well as a preparation method and application thereof. The chemical formula of the transition metal doped polyoxometallate cluster is Na34 [Co19 (OH) 12 (SiW10O37) 6]. 46H2O, and the molecular structure unit of the transition metal doped polyoxometallate cluster comprises [Co19 (OH) 12 (SiW10O37) 6] 34-subunit, 34 sodium ions and 46 lattice water molecules, wherein the [Co19 (OH) 12 (SiW10O37) 6] 34-subunit is centrosymmetric; the subunit is composed of a giant [Co19 (OH) 12] 26 < + > nanosheet and six [alpha-SiW10O37] 10 <-> in a coordination manner. The invention provides a transition metal doped polyoxometallate cluster containing a [Co19 (OH) 12] 26 < + > subunit, and the transition metal doped polyoxometallate cluster shows excellent OER (Optical Error Rate) performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of electrocatalytic oxygen evolution, and in particular relates to a transition metal-doped polyoxometalate cluster and a preparation method and application thereof. Background Art

[0002] Electrochemical decomposition of water to produce oxygen and hydrogen is of great significance for the storage and utilization of renewable energy. In the two half reactions of hydrogen evolution and oxygen evolution, the oxygen evolution reaction (OER, 2H2O→4H + +O2+4e – ) process consists of O–H bond breaking and O–O bond formation, involving a multi-step reaction of four electrons, so the oxygen evolution reaction has slower kinetics (higher overpotential). In order to overcome the high overpotential of OER, people have invested a lot of effort in developing OER electrocatalysts based on noble metals (such as Pt) and noble metal oxides (such as RuO2, IrO2). Although noble metals and their oxides are the most advanced OER electrocatalysts due to the high cost and low abundance of Pt and RuO2 / IrO2, their resource scarcity limits their commercial application. Therefore, the development of low-cost and abundant transition metal-based electrocatalysts as alternatives to noble metal-based catalysts is key to achieving efficient OER. In addition, structural optimization of catalysts by increasing the number of reaction active sites is also urgently needed for the development of OER catalysts with high activity and stability.

[0003] Polyoxometalates (POMs) are a well-known class of nanoscale metal-oxygen clusters with unique structural features that can be considered as model compounds for transition metal oxides. Transition metal-doped POMs are ideal candidates for OER photo / electrocatalysts due to their good adjustability and designability in elemental composition, atomic number, counterion type, valence state, and framework structure.

[0004] In the past decade, although some transition metal-doped polyoxometalate clusters and their OER research have been reported, there are still some shortcomings such as unstable catalysts, few catalytic active sites, unclear catalytic mechanism and OER performance inferior to commercial catalysts. Therefore, it is of continuous significance to explore new stable high-nuclear transition metal-doped polyoxometalate clusters for efficient OER. Summary of the invention

[0005] The main purpose of the present invention is to provide a transition metal-doped polyoxometalate cluster and a preparation method and application thereof, so as to overcome the deficiencies of the prior art.

[0006] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention includes: The embodiment of the present invention provides a transition metal doped polyoxometalate cluster, wherein the chemical formula of the transition metal doped polyoxometalate cluster is Na 34 [Co 19 (OH) 12 (SiW 10 O 37 )6]·46H2O, the molecular structural unit of the transition metal doped polyoxometalate cluster includes a centrosymmetric [Co 19 (OH) 12 (SiW 10 O 37 )6] 34– subunit, 34 sodium ions and 46 lattice water molecules; wherein the [Co 19 (OH) 12 (SiW 10 O 37 )6] 34– The subunit is composed of a giant [Co 19 (OH) 12 ] 26+ Nanosheets and six [ α -SiW 10 O 37 ] 10– Coordination composition, the [Co 19 (OH) 12 ] 26+ The nanosheet is composed of six two-vacancy Keggin-type [ α -SiW 10 O 37 ] 10– The groups are packed in a staggered manner.

[0007] The embodiment of the present invention further provides a method for preparing the aforementioned transition metal-doped polyoxometalate clusters, which comprises: Contain at least Na 10 [ α -SiW9O 34 ]·18H2O, Co source and 4,4'-((5-(4-(4 H The mixed reaction system of the invention comprises: -1,2,4-triazole-4-yl)phenoxy)-1,3-phenylene)bis(oxy))dibenzoic acid to prepare transition metal doped polyoxometalate clusters.

[0008] The embodiment of the present invention also provides the use of the aforementioned transition metal-doped polyoxometalate clusters in electrocatalytic oxygen evolution.

[0009] An embodiment of the present invention further provides an OER electrocatalyst, which includes the aforementioned transition metal-doped polyoxometalate cluster.

[0010] Compared with the prior art, the present invention has the following beneficial effects: (1) The transition metal-doped polyoxometalate clusters (cobalt-containing Keggin-type polyoxometalates) of the present invention exhibit superior OER performance compared to the existing cobalt-containing Dawson-type polyoxometalates; (2) The transition metal-doped polyoxometalate clusters of the present invention contain planar high-nuclear cobalt-oxygen clusters. Compared with the existing transition metal-doped polyoxometalate clusters, the planar high-nuclear cobalt-oxygen cluster structure helps to effectively expose the cobalt catalytic active sites, thereby improving its OER performance; (3) The planar type [Co 19 (OH) 12 ] 26+ The Co ions in the catalyst are connected by 12 hydroxyl bridges, which are more conducive to the synergistic catalysis of Co–O–Co compared with the existing oxygen atom connection, promoting efficient electron transfer and further improving its OER performance. (4) The transition metal-doped polyoxometalate clusters of the present invention have OER performance comparable to that of commercial noble metal catalysts (such as Pt, RuO2 and IrO2), and have good application prospects in electrocatalytic water oxidation; (5) The preparation process of the transition metal-doped polyoxometalate clusters of the present invention is simple, the synthetic raw materials are cheap and readily available, the reaction conditions are mild, and it is easy to produce in large quantities. BRIEF DESCRIPTION OF THE DRAWINGS

[0011] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0012] Figure 1a In a typical embodiment of the present invention, 19 (OH) 12 (SiW 10 O 37 )6] 34– Subunit a Illustration of the axis view; Figure 1b In a typical embodiment of the present invention, 19 (OH) 12 ] 26+ Illustration of the ball-and-stick structure model of nanosheets; Figure 1c In a typical embodiment of the present invention, 19 (OH) 12 (SiW10 O 37 )6] 34– Subunit b Illustration of the axis view; Figure 1d It is a sandwich type [Co 19 (OH) 12 (SiW 10 O 37 )6] 34– Simplified model diagram of the subunit; Figure 1e It is a typical embodiment of the present invention, wherein the Keggin type [ α -SiW 10 O 37 ] 10– Schematic representation of polyoxyanions; Figure 1f is a diagram of a compact {Co7} core fragment similar to the Anderson–Evans structure in a typical embodiment of the present invention; Figure 1g In a typical embodiment of the present invention, 19 (OH) 12 (SiW 10 O 37 )6] 34– Diagram of the -ABAB- arrangement pattern of subunits; Figure 2a In a typical embodiment of the present invention, Co 19 6W 60 X-ray powder diffraction pattern of the clusters; Figure 2b In a typical embodiment of the present invention, Co 19 6W 60 Thermogravimetric analysis of clusters; Figure 2c In a typical embodiment of the present invention, Co 19 6W 60 Clusters and α -SiW9O 34 ] 10– Infrared spectra of the precursor; Figure 2d In a typical embodiment of the present invention, Co 19 6W 60 UV-visible absorption spectrum of the clusters; Figure 2e In a typical embodiment of the present invention, Co 19 6W 60 Solid diffuse reflectance image of clusters; Figure 2fIn a typical embodiment of the present invention, Co 19 6W 60 Bandgap diagram of clusters; Figure 2g In a typical embodiment of the present invention, Co 19 6W 60 Mott–Schottky plot of clusters; Figure 2h In a typical embodiment of the present invention, Co 19 6W 60 The energy band structure of the cluster; Figure 3a~3d In a typical embodiment of the present invention, Co 19 6W 60 Cluster, SiW9, Co4(PW9)2, CoW 12 Electrochemical LSV curves, ECSA curves, EIS response graphs and Tafel curves of CoO; Figure 4 is Co used for OER electrocatalysis in a typical embodiment of the present invention 19 6W 60 Schematic diagram. DETAILED DESCRIPTION

[0013] In view of the defects of the prior art, the inventor of this case has proposed the technical solution of the present invention after long-term research and extensive practice. The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0014] Specifically, as one aspect of the technical solution of the present invention, the chemical formula of a transition metal-doped polyoxometalate cluster is Na 34 [Co 19 (OH) 12 (SiW 10 O 37 )6]·46H2O, the molecular structural unit of the transition metal doped polyoxometalate cluster includes a centrosymmetric [Co 19 (OH) 12 (SiW 10 O 37 )6] 34– subunit, 34 sodium ions and 46 lattice water molecules; wherein the [Co 19 (OH) 12 (SiW 10 O 37 )6]34– The subunit is composed of a giant [Co 19 (OH) 12 ] 26+ Nanosheets and six [ α -SiW 10 O 37 ] 10– Coordination composition, the [Co 19 (OH) 12 ] 26+ The nanosheet is composed of six two-vacancy Keggin-type [ α -SiW 10 O 37 ] 10– The groups are packed in a staggered manner.

[0015] In some preferred embodiments, the [Co 19 (OH) 12 ] 26+ The Co ion in the μ 3-OH bridge connection.

[0016] In some preferred embodiments, the [Co 19 (OH) 12 ] 26+ The six two-missing Keggin types [ α -SiW 10 O 37 ] 10– Group by μ 2-O bridge, μ 3-O bridge, μ 4-O bridge connection.

[0017] Another aspect of the embodiments of the present invention further provides a method for preparing the aforementioned transition metal-doped polyoxometalate clusters, which comprises: Contain at least Na 10 [ α -SiW9O 34 ]·18H2O, Co source and 4,4'-((5-(4-(4 H The mixed reaction system of the invention comprises: -1,2,4-triazole-4-yl)phenoxy)-1,3-phenylene)bis(oxy))dibenzoic acid to prepare transition metal doped polyoxometalate clusters.

[0018] In some preferred embodiments, the preparation method specifically comprises: Will Na 10 [ α -SiW9O 34 ]·18H2O, Co source, 4,4'-((5-(4-(4 H-1,2,4-triazol-4-yl)phenoxy)-1,3-phenylene)bis(oxy))dibenzoic acid is dispersed in a mixed solvent and the pH value is adjusted to 6.8-7.2 to form the mixed reaction system; Furthermore, the mixed reaction system is reacted at 115-135° C. for 3-5 days in a sealed state to obtain transition metal-doped polyoxometalate clusters.

[0019] Furthermore, the Co source includes CoCl2·6H2O and / or , but not limited to this.

[0020] Furthermore, the mixed solvent includes N,N-dimethylacetamide (denoted as: DMA) and water.

[0021] Furthermore, an alkaline solution is used to adjust the pH value to 6.8-7.2.

[0022] Furthermore, the alkaline solution includes sodium hydroxide solution and / or potassium hydroxide solution, but is not limited thereto.

[0023] Furthermore, the Na 10 [ α -SiW9O 34 ]·18H2O, Co source and 4,4'-((5-(4-(4 H The molar ratio of 1,2,4-triazol-4-yl)phenoxy)-1,3-phenylene)bis(oxy))dibenzoic acid is (0.02~0.06):(0.18~0.36):(0.06~0.16).

[0024] Another aspect of the embodiments of the present invention further provides the use of the aforementioned transition metal-doped polyoxometalate clusters in electrocatalytic oxygen evolution.

[0025] Another aspect of an embodiment of the present invention further provides an OER electrocatalyst, which includes the aforementioned transition metal-doped polyoxometalate cluster.

[0026] The present invention provides a novel transition metal doped polyoxometalate cluster, the chemical formula of which is Na 34 [Co 19 (OH) 12 (SiW 10 O 37 )6]·46H2O(denoted as: Co 19 6W 60 ), the subunit consists of six di-absent Keggin-type [ α -SiW 10 O 37 ] 10– The groups wrap around the giant [Co19 (OH) 12 ] 26+ Among all the polyacid-based OER catalysts developed so far, Co 19 6W 60 It is a transition metal-doped polyoxometalate cluster with the highest number of transition metal nuclei and the most hydroxyl bridges. 19 6W 60 The electrocatalytic OER platform shows an ultralow overpotential (at 10 mA cm) in alkaline aqueous solution (1 M KOH). –2 The overpotential relative to RHE at the current density is 328 mV, and the Tafel slope is 81 mV·dec –1 ). 19 6W 60 The electrocatalytic performance is better than that of previous polyacid catalysts and cobalt oxide. 19 6W 60 It can be regarded as one of the next generation of novel OER electrocatalysts.

[0027] The Co in the present invention 19 6W 60 The clusters show superior OER performance compared with the existing Dawson-type polyacids containing cobalt; the Co 19 6W 60 The cluster contains a planar high-nuclear cobalt-oxygen cluster. Compared with the existing transition metal-doped polyacid clusters, the planar high-nuclear cobalt-oxygen cluster structure helps to effectively expose the cobalt catalytic active sites, thereby improving its OER performance; the planar [Co 19 (OH) 12 ] 26+ The Co ions in the present invention are connected by 12 hydroxyl bridges, which is more conducive to the synergistic interaction of Co-O-Co compared with the existing oxygen atom connection, promoting efficient electron transfer and further improving its OER performance; the Co 19 6W 60 The clusters have OER performance comparable to that of industrial noble metal catalysts (such as Pt, RuO2 and IrO2), and have good application prospects in electrocatalytic water oxidation. 19 6W 60 The preparation process of the clusters is simple, the synthetic raw materials are cheap and easily available, the reaction conditions are mild, and they are easy to produce in large quantities.

[0028] The technical solution of the present invention is further described in detail below in conjunction with several preferred embodiments and drawings. This embodiment is implemented on the premise of the technical solution of the invention, and a detailed implementation method and specific operation process are given, but the protection scope of the present invention is not limited to the following embodiments.

[0029] Materials and test methods: The experimental materials used in the examples of the present invention can be purchased from conventional biochemical reagent companies unless otherwise specified. All chemicals are of reagent grade purity. Elemental analysis (EA) was performed using an elemental analyzer (Flash EA 1112 series, Thermo Electron Corporation) at 900 °C in an oxygen atmosphere with complete combustion. The samples were heated at a rate of 5 °C min in a nitrogen atmosphere. –1 Thermogravimetric analysis (TGA) was performed using a Perkin-Elmer Pyris Diamond SII thermal analyzer in the temperature range of room temperature to 800 °C. Powder X-ray diffraction (PXRD) patterns were measured on a Rigaku D / Max-2500 X-ray diffractometer operating at 40 kV and 100 mA, using a Cu target tube and a graphite monochromator. Infrared (IR) spectra of the material were obtained on a Bruker Tensor 27 spectrometer. Solid-state ultraviolet-visible absorption spectra (UV-Vis) and diffuse reflectance spectra (R%) were measured on a Hitachi UH4150 spectrophotometer at room temperature.

[0030] Example: Co 19 6W 60 Synthesis: Na 10 [ α -SiW9O 34 ]·18H2O (111.2 mg, 0.04 mmol), CoCl2·6H2O (49.9 mg, 0.21 mmol) and 4,4'-((5-(4-(4 H A mixture of 1,2,4-triazol-4-yl)phenoxy)-1,3-phenylene)bis(oxy)dibenzoic acid (acting as a template) (40.3 mg, 0.08 mmol) was ultrasonically dispersed in a mixed solvent of DMA (3.0 mL) and H2O (2.0 mL). The mixture was magnetically stirred for 1 hour, and then 1.0 mol·L –1 The pH value was adjusted to 6.8-7.2 by adding NaOH solution. The resulting suspension was sealed in a 25 mL polytetrafluoroethylene-lined reactor and reacted at 120 °C for three days. After the reactor was cooled to room temperature, purple block single crystals were obtained, which were washed with H2O and dried. Yield: 29%. Co 19 6W 60 The EA and ICP test results are (%): theoretical values: sodium 4.42, silicon 0.95, cobalt 6.33, tungsten 62.37; measured values: sodium 4.21, silicon 1.08, cobalt 6.57, tungsten 61.98.

[0031] Co 19 6W 60 X-ray single crystal test: Under a polarizing microscope, single crystals of appropriate size were selected for X-ray single crystal diffraction experiments at room temperature. Crystallographic data were collected by an Agilent Supernova X-ray single crystal diffractometer equipped with a graphite monochromator and a copper target light source. The single crystal structure was solved by the SHELXS (direct method) program in the Olex2 software, and the structure was refined by the SHELXL program (full matrix least squares method) in the Olex2 software. All non-hydrogen atoms were refined anisotropically. The hydrogen atoms on those water molecules were not located. The chemical formula was determined by combining crystallographic data, EA and TGA results. Table 1 is the detailed information of data collection and improvement.

[0032] Table 1 Co 19 6W 60 The main crystallographic data

[0033]

[0034] Electrochemical measurements: Co 19 6W 60 (1 mg) was ultrasonically dispersed in ethanol (200 μL) and nifion (10 μL), and carbon black (0.25 mg) was added and ultrasonically dispersed again. The above suspension was carefully dropped on carbon paper and dried in preparation for OER testing. All tests were studied using a three-electrode system, with a mercury sulfate electrode as the reference electrode and a platinum sheet as the counter electrode. All reported chemical potentials have been converted to potentials relative to the reversible hydrogen electrode (RHE). For all electrochemical experiments, unless otherwise stated, 1 M KOH solution (pH = 14) and 5 mV·s –1 All electrochemical tests were performed using a CHI 660C electrochemical workstation (Shanghai Chenhua, China).

[0035] X-ray crystal structure analysis: Single crystal structure analysis (Table 1) shows that Co 19 6W 60 Belongs to the monoclinic system, P 2(1) / n Space group, whose molecular structural unit consists of a centrosymmetric [Co 19 (OH) 12 (SiW 10 O 37 )6] 34– Polyoxyanions ( Figure 1a), 34 Na(I) ions and 46 lattice water molecules. 19 (OH) 12 (SiW 10 O 37 )6] 34– The polyoxo anion contains a novel [Co 19 (OH) 12 ] 26+ Transition metal clusters ( Figure 1b ), the transition metal nanocluster is composed of six divacant Keggin-type [ α -SiW 10 O 37 ] 10– Group ( Figure 1e ) are wrapped in a staggered manner, forming a typical sandwich structure ( Figure 1c and Figure 1d )。 19 (OH) 12 ] 26+ All 19 Co(II) ions in Figure 1b , shown in rose red) are roughly located in the same plane, forming planar hexagonal nanosheets based on edge-sharing {CoO6} and {CoO7} polyhedra. [Co 19 (OH) 12 ] 26+ The Co(II) ion in the μ 3–OH bridge ( Figure 1b , shown in blue). The planar hexagon [Co 19 (OH) 12 ] 26+ The structure consists of six two-missing Keggin types [ α -SiW 10 O 37 ] 10– Group by μ 2-O, μ 3-O and μ 4-O Bridge ( Figure 1b , shown in gray). 19 (OH) 12 ] 26+ The central Co(II) ion passes through six μ The 3-OH bridges connect to the six surrounding Co(II) ions, forming a compact {Co7} core fragment similar to the Anderson–Evans structure ( Figure 1f )。 19 (OH) 12 ] 26+The central Co(II) ion is coordinated in a regular hexacoordinated octahedral manner, with an average Co–O bond length of 2.138(6) Å.

[0036] In addition, in the formation of planar hexagonal [Co 19 (OH) 12 ] 26+ Nanosheet process, six two-vacancy Keggin type [ α -SiW 10 O 37 ] 10– The group can act as a structure-directing agent, and the twelve μ The 3-OH bridge can act as a structural stabilizer. 19 (OH) 12 (SiW 10 O 37 )6] 34– Subunit in bc The plane is arranged in a regular -ABAB- pattern ( Figure 1g ), free Na(I) ions and lattice water molecules occupy spatial positions through electrostatic attraction, forming a high-nuclear number transition metal [Co 19 (OH) 12 ] 26+ Cluster-doped polyoxometalate clusters. Because based on [Co 19 (OH) 12 ] 26+ Sandwich-type polyoxometalate clusters Co 19 6W 60 The transition metal-doped polyoxometalate clusters Co have strong hydrophilicity and contain multiple Co–O–Co and Co–OH–Co synergistic catalytic active sites. 19 6W 60 It can be used as an ideal candidate material for efficient OER electrocatalysis.

[0037] Co 19 6W 60 Basic characterization: X-ray powder diffraction: transition metal doped polyoxometalate clusters Co 19 6W 60 X-ray powder diffraction ( Figure 2a ) The results show that the diffraction information of the prepared powder sample is consistent with that of the transition metal doped polyacid clusters Co 19 6W 60 This is consistent with the single crystal diffraction theoretical simulation information, which means that the prepared powder sample is pure phase Co 25 6W 60 Nanoclusters.

[0038] Thermogravimetric analysis: transition metal doped polyoxometalate clusters Co 19 6W 60 X-ray powder diffraction ( Figure 2b ) The results showed that Co 19 6W 60 The weight loss of can be divided into two steps. Between 19 and 110 °C, the first weight loss is 4.57% (calculated value is 4.69%), involving the release of 46 lattice water molecules. Between 110 and 800 °C, the weight of the compound slowly decreases by 7.51%, which may be due to the release of [Co 19 (OH) 12 (SiW 10 O 37 )6] 34– [Co 19 (OH) 12 ] 26+ In short, Co 19 6W 60 Sandwich type [Co 19 (OH) 12 (SiW 10 O 37 )6] 34– The clusters have good thermal stability in the temperature range of 19~110 °C and can be used for OER electrocatalytic application research.

[0039] Infrared spectroscopy: transition metal doped polyoxometalate clusters Co 19 6W 60 The infrared spectrum of Figure 2c . At high wave number 3670~2920 cm –1 In this region, the strong and broad peak is attributed to [Co 19 (OH) 12 ] 26+ Nanoclusters and lattice water molecules ν (O–H) stretching vibration. In the low wavenumber region, 991, 951, 898, and 782 cm –1 The four characteristic vibration peaks at are respectively attributed to the Keggin type [ α -SiW 10 O 37 ] 10– Anionic structural framework v (W–O t ), v (Si–O a ), v (W–O b )and v (W–O c )'s asymmetric stretching vibration.19 6W 60 With three missing Keggin type [ α -SiW9O 34 ] 10– There are obvious differences in the infrared spectra of the polyacid reaction raw materials, indicating that [ α -SiW9O 34 ] 10– The structure of the precursor changes during the hydrothermal reaction. 19 6W 60 Compared with the two-missing Keggin type reported in the literature [ α -SiW 10 O 37 ] 10– Comparison of infrared spectra of polyacids, Co 19 6W 60 In ν (WO t ) vibration peak showed an obvious red shift (45 cm –1 ), which is due to the sandwich type [Co 19 (OH) 12 (SiW 10 O 37 )6] 34– This is due to the strong interaction between the terminal oxygen atoms of the cluster and the charge-compensating cations. 19 6W 60 The results of infrared spectrum analysis are consistent with those of X-ray single crystal structure analysis.

[0040] Solid-state UV-visible spectroscopy: transition metal-doped polyoxometalate clusters Co 19 6W 60 The solid-state UV-visible spectrum of Figure 2d .Co 19 6W 60 The solid-state UV-visible absorption spectrum of NH4Cl2 showed a strong and broad absorption signal in the range of 200-470 nm, which was attributed to the O b(c) →W pπ – dπ Charge transfer transition. However, O t →W pπ – dπ The charge transfer transition has a higher absorption energy, and its absorption peak is blue-shifted to the near-ultraviolet region below 190 nm. In the range of 470-600 nm, Co 19 6W 60 The strong absorption peak corresponds to the Co(II)-centered d – d This is consistent with previous literature reports. In order to obtain its band gap energy, the Co19 6W 60 Solid-state diffuse reflectance spectra and Kubelka–Munk functions. 19 6W 60 The band gap energy of Co is determined as the intersection between the energy axis and the line extrapolated from the linear part of the absorption edge in the Tauc plot of the Kubelka-Munk function and the photon energy. 19 6W 60 UV-Vis diffuse reflectance spectrum ( Figure 2e )and( αhv ) 1 / 2 The relationship between energy ( Figure 2f ) characterization determined that its energy band value was 1.94 eV. These results indicate that Co 19 6W 60 It is an ideal semiconductor-type high-nuclear polyacid cluster, and such a low band gap energy value is rarely observed in previously reported related polyacids.

[0041] To further evaluate the band edge position, Mott–Schottky electrochemical measurements were performed on Co 19 6W 60 The semiconductor type and band potential (usually considered to be the Fermi level ( E f )) conducted research ( Figure 2g ), the results showed that Co 19 6W 60 It is a typical n -type semiconductor material. Co 19 6W 60 The flat band potential of is estimated to be –0.277 eV (relative to Ag / AgCl), which is converted to –0.079 eV relative to the reversible hydrogen electrode (RHE). n The bottom of the conduction band (CB) of a -type semiconductor is about 0.200 eV negative compared to its conduction band potential, so Co 19 6W 60 The CB minimum is estimated to be around –0.279 eV ( Figure 2h ). Since the bandgap value estimated from solid-state diffuse reflectance spectroscopy is 1.94 eV, its valence band (VB) maximum value should be 1.661 eV (relative to RHE). Based on the above analysis, Co 19 6W 60 Clusters are very suitable for electrocatalytic oxygen evolution.

[0042] Co 19 6W 60 Research on electrocatalytic oxygen evolution: To evaluate Co 196W 60 The electrocatalytic OER performance of the catalyst was tested by linear sweep voltammetry (LSV) under alkaline conditions (pH = 14). Figure 3a As shown, at 10 mA·cm –2 At a current density of Co 19 6W 60 The overpotential is only 328 mV, which is lower than [ α -SiW9O 34 ] 10– (690 mV for SiW9), [Co4(H2O)2( α -PW9O 34 )2] 10– (410mV for Co4(PW9)2), [α-CoW 12 O 40 ] 6– (CoW 12 400 mV) and CoO (503 mV). Comparison of these results shows that Co 19 6W 60 The plane hexagon in [Co 19 (OH) 12 ] 26+ Nanosheets play an important role in OER electrocatalysis. In order to evaluate the real electrocatalytic activity of the material and the specific number of active sites, Co 19 6W 60 Electrochemically active surface area (ECSA) tests were performed. Figure 3b As shown, Co 19 6W 60 The ECSA value of the cluster is 16.9 mF·cm –2 , both higher than SiW9 (1.9 mF·cm –2 )、Co4(PW9)2(3.9mF·cm –2 )、CoW 12 (3.8 mF·cm –2 ) and CoO (0.9 mF·cm –2 ). This result is consistent with the results of LSV, indicating that Co 19 6W 60 The clusters have more electrocatalytic active sites than other catalysts and have better electrocatalytic activity for OER. 19 6W 60 To investigate the source of the excellent OER activity of the clusters, an electrochemical impedance spectroscopy (EIS) experiment was performed. The EIS test results ( Figure 3c ) shows that Co 19 6W 60The charge transfer resistance of the clusters (2.97 Ω) is smaller than that of SiW9 (15.00 Ω), Co4(PW9)2 (5.34 Ω), and CoW 12 (5.59 Ω) and CoO (9.80 Ω), demonstrating that Co 19 6W 60 The fast electron transfer performance of clusters in electrochemical reactions. Figure 3d As shown, Co 19 6W 60 The Tafel slope of the cluster is 81 mV·dec –1 , which are significantly lower than SiW9 (487 mV·dec –1 )、Co4(PW9)2(148 mV·dec –1 )、CoW 12 (92 mV·dec –1 ) and CoO (232 mV·dec –1 ), which proves that Co 19 6W 60 These OER results show that the hexagonal [Co 19 (OH) 12 ] 26+ Sandwich Co 19 6W 60 Clusters can be used as potential molecular platforms for modifying the electronic structure of electrocatalysts. In summary, the present invention successfully synthesized sandwich-type transition metal cobalt-doped polyoxometalate clusters. 19 6W 60 The cluster is composed of a huge hexagonal [Co 19 (OH) 12 ] 26+ Nanosheets and six staggered two-vacancy Keggin-type [ α -SiW 10 O 37 ] 10– Composition of multiple oxygen anions. 19 6W 60 The clusters are one of the best candidate electrocatalysts for electrochemical oxygen evolution in polyacids. In alkaline aqueous solution (1 M KOH), Co 19 6W 60 The clusters have an ultra-low overpotential (10 mA cm –2 At current density, 328 mV relative to RHE) and 81 mV·dec –1 The Tafel slope of Co is comparable to that of the Keggin-type polyacid electrocatalysts containing Co reported in the literature. 19 6W60 The superior performance of the proposed method is attributed to the rational design of multiple catalytic active sites, which are derived from [Co 19 (OH) 12 ] 26+ Nanosheets. These results provide a feasible strategy for the rational design and controllable construction of high-nuclear number transition metal-doped polyacid catalysts. This invention opens up a new way to use high-nuclear number transition metal-doped polyacid clusters as potential electrocatalysts for energy storage and conversion in the future.

[0043] In addition, the inventors of this case also referred to the aforementioned embodiments and conducted experiments with other raw materials, process operations, and process conditions described in this specification, and obtained relatively ideal results.

[0044] It should be understood that the technical solution of the present invention is not limited to the above-mentioned specific implementation cases. Any technical deformation made according to the technical solution of the present invention without departing from the scope of protection of the purpose of the present invention and the claims shall fall within the protection scope of the present invention.

Claims

1. A transition metal-doped polyoxometalate cluster, characterized in that: The chemical formula of the transition metal doped polyoxometalate cluster is Na 34 [Co 19 (OH) 12 (SiW 10 O 37 )6]·46H2O, the molecular structural unit of the transition metal doped polyoxometalate cluster includes a centrosymmetric [Co 19 (OH) 12 (SiW 10 O 37 )6] 34– subunit, 34 sodium ions and 46 lattice water molecules; wherein the [Co 19 (OH) 12 (SiW 10 O 37 )6] 34– The subunit is composed of a giant [Co 19 (OH) 12 ] 26+ Nanosheets and six [ α -SiW 10 O 37 ] 10– Coordination composition, the [Co 19 (OH) 12 ] 26+ The nanosheet is composed of six two-vacancy Keggin-type [ α -SiW 10 O 37 ] 10– The groups are packed in a staggered manner.

2. The transition metal-doped polyoxometalate cluster according to claim 1, characterized in that: The [Co 19 (OH) 12 ] 26+ The Co ion in the μ 3-OH bridge connection; And / or, the [Co 19 (OH) 12 ] 26+ The six two-missing Keggin types [ α -SiW 10 O 37 ] 10– Group by μ 2-O bridge, μ 3-O bridge, μ 4-O bridge connection.

3. The method for preparing transition metal-doped polyoxometalate clusters according to claim 1 or 2, characterized in that: include: Contain at least Na 10 [ α -SiW9O 34 ]·18H2O, Co source and 4,4'-((5-(4-(4 H The mixed reaction system of the invention comprises: -1,2,4-triazole-4-yl)phenoxy)-1,3-phenylene)bis(oxy))dibenzoic acid to prepare transition metal doped polyoxometalate clusters.

4. The preparation method according to claim 3, characterized in that: Specifically include: Will Na 10 [ α -SiW9O 34 ]·18H2O, Co source, 4,4'-((5-(4-(4 H -1,2,4-triazol-4-yl)phenoxy)-1,3-phenylene)bis(oxy))dibenzoic acid is dispersed in a mixed solvent and the pH value is adjusted to 6.8-7.2 to form the mixed reaction system; Furthermore, the mixed reaction system is reacted at 115-135° C. for 3-5 days in a sealed state to obtain transition metal-doped polyoxometalate clusters.

5. The preparation method according to claim 4, characterized in that: The Co source includes CoCl2·6H2O and / or .

6. The preparation method according to claim 4, characterized in that: The mixed solvent includes N,N-dimethylacetamide and water.

7. The preparation method according to claim 4, characterized in that: The pH value is adjusted to 6.8-7.2 using an alkaline solution; preferably, the alkaline solution includes a sodium hydroxide solution and / or a potassium hydroxide solution.

8. The preparation method according to claim 3, characterized in that: The Na 10 [ α -SiW9O 34 ]·18H2O, Co source and 4,4'-((5-(4-(4 H The molar ratio of 1,2,4-triazol-4-yl)phenoxy)-1,3-phenylene)bis(oxy))dibenzoic acid is (0.02~0.06):(0.18~0.36):(0.06~0.16).

9. Use of the transition metal-doped polyoxometalate clusters according to claim 1 or 2 in electrocatalytic oxygen evolution.

10. An OER electrocatalyst, characterized in that It comprises the transition metal-doped polyoxometalate cluster as described in claim 1 or 2.